Author Correction: Msx1 loss suppresses formation of the ectopic crypts developed in the Apc-deficient small intestinal epithelium - Horazna, Monika; Janeckova, Lucie; Svec, Jiri; Babosova, Olga; Hrckulak, Dusan; Vojtechova, Martina; Galuskova, Katerina; Sloncova, Eva; Kolar, Michal; Strnad, Hynek; Korinek, Vladimir (Scientific reports, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.